Maternal Serum VEGF Predicts Abnormally Invasive Placenta Better than NT-proBNP: a Multicenter Case-Control Study - Schwickert, Alexander (Reprod Sci, 2020)
The aim of this study was to test if maternal serum vascular endothelial growth factor (VEGF) or N-terminal pro B-type natriuretic peptide (NT-proBNP) predicts abnormally invasive placenta (AIP) better. Secondary objective was to test whether the serum levels of VEGF and NT-proBNP can predict the degree of invasion. In a multicenter case–control study design, gestational age-matched serum samples from pregnant women with AIP (n = 44) and uncomplicated pregnancies (n = 55) who had been enrolled at Charité – Universitätsmedizin Berlin, Germany and Centre Hospitalier Régional de la Citadelle in Liège, Belgium were analyzed. Maternal blood serum VEGF and NT-proBNP levels were immunoassayed from samples taken immediately before delivery (GA median: 35 weeks). Biomarker levels were compared between AIP and control group. The correlation of biomarker levels with the clinical AIP degree was assessed. The predictive biomarker ability was characterized through a multivariate regression model and receiver operating characteristic curves. Women with AIP had significantly lower maternal serum VEGF levels (AIP mean 285 pg/ml, 95% CI 248–322, vs. control: 391 pg/ml, 95% CI 356–426, p < 0.01) and higher NT-proBNP levels (AIP median 329 pg/ml, IQR 287–385, vs. control 295 pg/ml, IQR 273–356, p = 0.03). Maternal serum VEGF levels were able to predict AIP better (AUC = 0.729, 0.622–0.836, p < 0.001; VEGF + number of previous cesarean deliveries: AUC = 0.915, 0.853–0.977, p < 0.001). Maternal serum VEGF levels correlated inversely with the clinical AIP degree (r = − 0.32, p < 0.01). In short, maternal serum VEGF, more than NT-proBNP, can help in predicting AIP and hints at the degree of invasion.